Extracellular ATP increases cytoplasmic free Ca2+ concentration in clonal insulin-producing RINm5F cells. A mechanism involving direct interaction with both release and refilling of the inositol 1,4,5-trisphosphate-sensitive Ca2+ pool. - Arkhammar, P; Hallberg, A; Kindmark, H; Nilsson, T; Rorsman, P; Berggren, P (1990)
Effects of extracellularly applied ATP (added as disodium salt) on stimulus-secretion coupling were investigated in clonal insulin-producing RINm5F cells. Cytoplasmic free Ca2+ concentration [( Ca2+]i), electrical activity, membrane potential, formation of InsP3 and insulin release were measured. Addition of ATP in a Ca2(+)-containing medium promoted a rapid rise in [Ca2+]i, which was followed by a slow decline towards the basal level. In a Ca2(+)-free medium, the ATP-induced increase in [Ca2+]i was smaller, but still enough to elicit insulin secretion. Upon normalization of the extracellular Ca2+ concentration, the response to ATP recovered instantaneously. The presence of glucose in the incubation medium was a prerequisite to obtain a pronounced effect of ATP in the absence of extracellular Ca2+. However, glucose did not enhance the response to ATP in a Ca2(+)-containing medium. The effect of ATP was dose-dependent, with a clearly detectable increase in [Ca2+]i at 1 microM and a maximal response being obtained at 200 microM-ATP. The response to ATP was unaffected by activating adenylate cyclase by forskolin, but was abolished by 10 nM of the phorbol ester phorbol 12-myristate 13-acetate. The effects of ATP on [Ca2+]i could not be accounted for by a generalized increase in plasma-membrane permeability, as evident from the failure of the nucleotide to increase the fluorescence of the nuclear stain ethidium bromide. After stimulation with ATP there was an increase in membrane potential, in both the absence and the presence of extracellular Ca2+. Blockage of the voltage-activated Ca2+ channals with D-600, in a Ca2(+)-containing medium, decreased the effect of ATP on [Ca2+]i slightly. Patch-clamp measurements using the cell-attached patch configuration revealed that the RINm5F cells produce spontaneous action potentials, the frequency of which increased markedly on addition of ATP. Whole-cell recordings demonstrated that the increase in spike frequency was not associated with the development of an inward current, but was rather accountable for by a decrease in the activity of the ATP-regulated K+ channels. Addition of 200 microM-ATP stimulated phospholipase C activity, as evident from the formation of InsP3, both in the absence and in the presence of extracellular Ca2+. Thus in the absence of extracellular Ca2+ the stimulatory effect of ATP on insulin release can be explained by InsP3-induced mobilization of intracellularly bound Ca2+. Hence, in the RINm5F cells extracellular ATP acts in a manner similar to other Ca2(+)-mobilizing agents.(ABSTRACT TRUNCATED AT 400 WORDS)